(untitled) (International Journal of Innovative Technologies in Economy, 2021)
The article aims to calculate the separate elements of the financial strategy of the NKR energy system and to carry out a factor analysis. Using the Kaufmann-Calibardi method, the coefficients of flexibility of electricity consumption by GDP were estimated, showing the causes of the shadow economy in the Artsakh Republic depending on the volume of electricity. Based on the annual statistics of electricity consumption and real GDP in the period of 2000-2019, the years were emphasized, as a result of which the fact that it is a calculated value of 1 substantiates the fact that the higher the electricity consumption, the higher the GDP should be, but obtained the results are not equal to 1 (greater than or less than 1), so the size of the shadow was calculated in those years.